MITIGASI LEARNING LOSS PASCA PANDEMI COVID-19 MELALUI MODEL PEMBELAJARAN PROJECT-BASED LEARNING BERDIFERENSIASI - Hibban, Muhammad Arkan; Pramono, Didi (Universitas Negeri Malang, 2024)
LEARNING LOSS MITIGATION AFTER THE COVID-19 PANDEMICTHROUGH PROJECT-BASED LEARNING DIFFERENTIATION LEARNINGMODEL COVID-19's existence in Indonesia has led to several new issues, particularly in education, oneof which is students' learning loss. This study aims to analyze how teachers mitigate learning lossand identify the impact of implementing project-based learning differentiation learning models.The methodology employed in this study takes a qualitative approach, combining primary datasources from interviews and observations along with secondary data from written sources suchas books and journal articles. As a validity test for this study, source triangulation with narrativedata presentation was used. Changes in learning settings induced by the COVID-19 pandemichave resulted in learning loss in students, thus teachers must act immediately using creativelearning models to reduce it. Students receive advantages from implementing this project-basedlearning differentiation methodology in terms of psychological outcomes. The real impact felt bystudents such as learning more fun, being motivated in class, and feeling comfortable during thelearning process is considered to be able to mitigate the occurrence of learning loss in studentsat SMAN 11 Semarang. Hadirnya COVID-19 di Indonesia membuat munculnya berbagai permasalah baru, tak terkecualipada bidang pendidikan dimana terdapat istilah baru pada siswa yaitu learning loss. Penelitianini bertujuan menganalisis bagaimana guru melakukan mitigasi learning loss dan mengidentifikasidampak implementasi model pembelajaran project based learning berdiferensiasi. Metode yangdigunakan dalam penelitian ini menggunakan pendekatan kualitatif dengan menggunakansumber data wawancara dan observasi sebagai data primer serta dokumentasi, buku, dan artikeljurnal sebagai data sekunder. Uji validitas penelitian ini menggunakan tiranggulasi sumberdengan penyajian data berupa naratif. Perubahan kondisi belajar karena pandemi COVID-19kemarin hingga saat ini menimbulkan terjadinya learning loss pada siswa, hingga guru harusbertindak cepat dengan mengimplementasikan model pembelajaran project based learningberdiferensiasi sebagai cara untuk mitigasi terjadinya learning loss pada siswa. Penggunaanmodel pembelajaran ini menunjukan perubahan psikologi dari siswa. Adanya dampak nyata yangdirasakan oleh siswa seperti belajar lebih menyenangkan, termotivasi dalam pembelajaran dikelas, dan merasa nyaman ketika proses pembelajaran dirasa mampu memitigasi terjadinyalearning loss pada siswa di SMAN 11 Semarang.